Managing Change in Vilnius University Library: New Partnerships and Innovative Services - Prokopčik, Marija; Krivienė, Irena (Bibliotheca Lituana, 2014)
The objective of this article is to ascertain most significant fields of the academic library activities, which have an impact on strengthening the library’s role as a partner in academic community, as well as to assess VUL capacities to see what kind of current or future activities may contribute to the building-up of such role in VU community. Analysis of recent LI S literature reveals the key trends in development of academic libraries, their innovative change and challenges – open access, managing of research data; research support; research assessment, scientific research; allows to analyse one particular library in order to see if and at what scale these trends can be traced in VUL . It was established that VUL contributes to practical implementation of open access, collaborates with VU and academic community in the projects of research data management, carries out bibliometric research, helps to form research support services, promotes the Library’s scholarly research and contributes to formation of the institution’s research potential. Description of new activities is important for the management of change. Adjustment of organizational structure, introduction of new positions and their description facilitate achievement of this purpose. It allows informing academic and library community about new activities and functions of the library; the Library assumes obligation to develop these activities, and employees are encouraged to meet high qualification requirements, whereas the Library looks for the ways to improve competencies of the personnel.
Keywords: none